James's will-to-believe doctrine : a heretical view - Wernham, James C. S. (McGill-Queen's University Press, 1987)
In 1896 William James published an essay entitled The Will to Believe, in which he defended the legitimacy of religious faith against the attacks of such champions of scientific method as W.K. Clifford and Thomas Huxley. James's work quickly became one of the most important writings in the philosophy of religious belief. James Wernham analyses James's arguments, discusses his relation to Pascal and Renouvier, and considers the interpretations, and misinterpretations, of James's major critics. Wernham shows convincingly that James was unaware of many destructive ambiguitities in his own doctrines and arguments, although clear and consistent in his view that our obligation to believe in theism is not a moral but a prudential obligation -- a foolish-not-to-believe doctrine, rather than a not-immoral-to-believe one. Wernham also shows that the doctrine is best read as affirming the wisdom of gambling that God exists, a notion which James failed to distinguish from believing and which, among other things, he explicitly identified with faith. James's pragmatism, a theory concerning the meaning of truth, is shown to be quite distinct from the doctrine of The Will to Believe. In concentrating on a careful analysis of this doctrine of the will-to-believe, Wernham not only makes a major contribution to understanding James's philosophy, but also clarifies issues in the philosophy of religion and in the analysis of belief and faith.